2010
DOI: 10.1177/1534765609347550
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate preabortion counseling and decision conflict as predictors of subsequent relationship difficulties and psychological stress in men and women.

Abstract: The purpose of this study was to examine associations between perceptions of preabortion counseling adequacy and partner congruence in abortion decisions and two sets of outcome variables involving relationship problems and individual psychological stress. Data were collected through online surveys from 374 women who had a prior abortion and 198 men whose partners had experienced elective abortion. For women, perceptions of preabortion counseling inadequacy predicted relationship problems, symptoms of intrusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 112 publications
1
17
1
2
Order By: Relevance
“…These losses resulted in immediate, painful injury as well as a forfeiture of the future in the sense that the men were grieving all that could have been but was lost forever after the abortion. Whereas other studies have reported profound grief among men whose partners abort (e.g., Coyle & Rue, ; McAll &McAll, ; Poggenpoel & Myburgh, ; Speckhard & Rue, ), this study is the first to draw attention to the persistence of men's grief over time and strongly suggests that some men may need professional help in resolving their grief.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…These losses resulted in immediate, painful injury as well as a forfeiture of the future in the sense that the men were grieving all that could have been but was lost forever after the abortion. Whereas other studies have reported profound grief among men whose partners abort (e.g., Coyle & Rue, ; McAll &McAll, ; Poggenpoel & Myburgh, ; Speckhard & Rue, ), this study is the first to draw attention to the persistence of men's grief over time and strongly suggests that some men may need professional help in resolving their grief.…”
Section: Discussioncontrasting
confidence: 68%
“…Rather, reports indicate that men tend to find the experience to be distressing, with a large majority of them describing abortion as a difficult experience that left them with lingering and disturbing thoughts (Shostak, , ; Shostak & McLouth, ). In studies of men whose partners underwent abortions, a number of adverse outcomes have been reported, including ambivalence (Kero & Lalos, , ), feelings of responsibility or culpability (Reich & Brindis, ; Rodrigues & Hoga, ), helplessness (Coyle & Rue, ; Hallden & Christensson, ), anxiety (Coyle & Rue, ; Schelotto, & Arcuri, ), posttraumatic stress reactions (Coyle, Coleman, & Rue, ; Lauzon, Roger‐Achim, Achim, & Boyer, ; Robson, ), anger (Naziri, ), guilt (Rothstein, ; Rue, ), and grief (Coyle & Rue, ; Speckhard & Rue, ). The grief may be experienced as disenfranchised grief (Coyle & Rue, ), complicated mourning (Speckhard & Rue, ), or depression (DuBois‐Bonnefond & Galle‐Tessonneau, ; McAll &McAll, ; Stern, ).…”
Section: Men and Abortionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, if childhood adversities are associated with having subsequent abortions, then programs that address the consequences of childhood adversities should include components on unintended pregnancy. Second, an increasing number of published papers claim that abortion harms women’s mental health (e.g., Coleman, 2011;Coleman, Coyle, Shuping, & Rue, 2009; Coyle, Coleman, & Rue, 2010). However, these papers usually do not take into account a wide range of early childhood adversities.…”
Section: Introductionmentioning
confidence: 99%